Optimization of the Treatment Algorithm of Patients with Low Resistance to Antiepileptic Drugs Using Pharmacogenetic Tests (Eurasian Medical Research Periodical, 2022)
The study of pharmacogenetic aspects of pharmacoresident epileptic patients is very little studied in medicine. To study the pharmacokinetics of convulex using therapeutic drug monitoring and pharmacogenetic testing to optimize the treatment of patients with epilepsy